Antifriction and wear-resistant sealing coating for ceramic matrix composite material and preparation method of antifriction and wear-resistant sealing coating
By preparing a coating of 7 wt% Y2O3-stable ZrO2-based self-lubricating layer and pure Si transition layer on the ceramic-based composite, the problems of high friction coefficient and high wear rate in the ceramic-based composite are solved, and low friction and low wear are achieved The effect extends the service life of the coating.
Patent Information
- Application Number
- CN202411472856.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The existing high-temperature tight-seal coatings have problems with high friction coefficient and high wear rate in ceramic matrix composite materials, which leads to the blades being easily worn under extreme conditions such as high pressure and high speed friction, high temperature gradient, and strong vibration impact, and lack of suitable Seal tight coating to extend the engine life.
Using a ceramic-based composite coating composed of 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer and a pure Si transition layer, it was prepared on the surface of C/SiC composite material by supersonic plasma spraying technology, combined with the collaborative lubrication of YSZ, CaF2, Mo and Ag It acts to form a coating with low coefficient of friction and low wear rate.
It effectively reduces friction on the coating surface, slows down the wear of the blades and the turbine outer ring, extends the service life of the coating, and shows good friction and wear performance under high temperature environments.
Smart Images

Figure CN119241281A_ABST
Abstract
Description
Technical field:
[0001] The invention belongs to the technical field of coating materials, and in particular relates to a friction-reducing, wear-resistant sealing coating for ceramic-based composite materials and a preparation method thereof. Background technology:
[0002] For more than half a century, abradable seal coatings have been used in the boost and turbine stages of gas turbines to reduce the gap between rotating and stationary parts, making a significant contribution to protecting blades and reducing fuel consumption and greenhouse gas emissions.
[0003] As the intake temperature of future aircraft engines increases, ceramic-based composite materials such as SiC / SiC and C / SiC will replace existing high-temperature alloy components in turbine applications. Although ceramic-based composite materials have shown great potential, there is currently a lack of a sealing coating that can match them. Existing high-temperature sealing coatings have problems such as high friction coefficient and high wear rate. The blades are very likely to suffer severe wear from the coating under extreme working conditions such as high pressure and high-speed friction, high temperature gradient, strong vibration impact, low lubrication and strong oxidation. Therefore, it is urgent to develop a special sealing coating for ceramic-based composite materials with high reliability, long life, low friction coefficient and low wear rate to reduce the friction on the coating surface, slow down the wear of the blades and the main part of the turbine outer ring, and extend the service life of the engine. Summary of the invention:
[0004] In order to solve the technical problems existing in the above-mentioned background technology, the present invention provides a friction-reducing and wear-resistant sealing coating for ceramic-based composite materials and a preparation method thereof. The ceramic-based abradable sealing coating has Si as a bonding layer and a 7YSZ (7wt% Y2O3 stabilized ZrO2) composite coating as a surface coating, has a low friction coefficient and wear rate, and is expected to reduce the mechanical damage caused by mutual friction between the engine blades and the turbine outer ring during service, enhance the performance benefits of the coating and extend its service life.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows: A first aspect of the present invention provides a friction-reducing and wear-resistant sealing coating for ceramic-based composite materials, wherein the friction-reducing and wear-resistant sealing coating comprises a transition layer adhered to a ceramic substrate layer and a 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer.
[0006] As a further illustration of the present invention, the ceramic matrix layer is a C / SiC composite material layer; and / or the transition layer is a pure Si transition layer.
[0007] As a further illustration of the present invention, the 7wt% Y2O3 stabilized ZrO2-based self-lubricating layer is composed of the following raw material components in percentage by weight: 7wt% Y2O3 stabilized ZrO2 40%-45%, CaF2 35%-40%, Mo 6%-12%, and Ag 8%-14%.
[0008] A second aspect of the present invention provides a method for preparing a friction-reducing and wear-resistant sealing coating for a ceramic-based composite material, comprising the following steps: Step 1: Select 7wt% Y2O3 stabilized ZrO2, CaF2, Mo and Ag powders as raw materials, and ball mill and mix them according to the raw material mass ratio of 7wt% Y2O3 stabilized ZrO2 40%-45%, CaF2 35%-40%, Mo 6%-12% and Ag 8%-14% respectively; Step 2: Drying the powder obtained in step 1 and the pure Si powder to pretreat the surface of the C / SiC composite material; Step 3: Use pure Si powder to prepare a pure Si transition layer on the surface of the C / SiC composite material matrix, and use the mixed powder obtained in step 1 to prepare a 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer on the surface of the pure Si transition layer.
[0009] As a further illustration of the present invention, the powder particle size of the raw materials in step 1 is 40-150 μm, the ball milling parameters are a rotation speed of 150-200 Hz, a ball milling time of 0.5-1 h, and a ball-to-material ratio of 5:1.
[0010] As a further illustration of the present invention, the pretreatment process of the surface of the C / SiC composite material in step 2 includes: The surface of the C / SiC substrate was polished with a diamond grinding disc, and the edges were chamfered, and finally ultrasonically cleaned and dried.
[0011] As a further illustration of the present invention, the pure Si transition layer and the 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer in step 3 are both prepared by supersonic plasma spraying.
[0012] As a further illustration of the present invention, the spraying parameters used for the pure Si transition layer are: spraying power 30-35Kw, powder feeding rate 1r / min, spraying distance 10cm, protective gas is argon, flow rate is 6L / min, and pressure is 1.05MPa.
[0013] As a further illustration of the present invention, the spraying parameters used for the 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer are: spraying power 40-45Kw, powder feed rate 2r / min, spraying distance 10cm, protective gas is argon, flow rate is 6L / min, and pressure is 1.05MPa.
[0014] As a further illustration of the present invention, the thickness of the pure Si transition layer prepared in step 3 is 180-200 μm, and the thickness of the self-lubricating layer is 400-500 μm.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The ceramic-based composite coating provided by the present invention is composed of a matrix phase 7YSZ and a plurality of solid lubricating phases, has no obvious defects such as holes and cracks inside, and the composite coating is tightly combined with the matrix. Through testing, it is found that the coating has good friction and wear performance at high temperatures, can avoid serious friction damage between the coating and the blade, effectively protect the blade and extend the service life. Description of the drawings:
[0016] Figure 1 The cross-sectional morphology of the gradient YSZ ceramic-based abradable sealing coating prepared by supersonic plasma spraying in Example 1 under the backscattering mode; Figure 2 is a curve showing the change of the friction coefficient of the YSZ ceramic-based abradable sealing coating in Example 1 at 400°C over time; Figure 3 The wear rate of the wear spot measured and calculated by a three-dimensional profilometer after the YSZ ceramic-based abradable sealing coating in Example 1 was subjected to a 400°C friction and wear test;
[0017] Figure 4 The cross-sectional morphology of the gradient YSZ ceramic-based abradable sealing coating prepared by supersonic plasma spraying in Example 2 under the backscattering mode; Figure 5 is a curve showing the change of the friction coefficient of the YSZ ceramic-based abradable sealing coating at 800°C over time in Example 2; Figure 6 The wear rate of the wear spot of the YSZ ceramic-based abradable sealing coating in Example 2 is measured and calculated using a three-dimensional profilometer after the coating has been subjected to a friction and wear test at 800°C. Specific implementation method:
[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The present invention provides a method for preparing a friction-reducing and wear-resistant sealing coating for ceramic-based composite materials. The overall idea is to use C / SiC composite materials as the matrix, design the proportion of coating raw material components, and use evenly mixed 7YSZ, CaF2, Mo and Ag mixed powders as powders for supersonic plasma spraying. Supersonic plasma spraying is used to prepare a self-lubricating composite coating with a certain hardness and porosity and good bonding with the matrix on the surface of the C / SiC composite material. Then, a reciprocating friction device is used to test the coating surface to obtain the friction coefficient curve and corresponding wear rate of the coating under certain experimental conditions, so as to determine the role of the lubricating phase in the coating in resisting friction damage, and finally reduce the friction coefficient and wear rate of the coating, effectively improve the poor abradability of the ceramic-based sealing coating, and balance the conflict between the friction coefficient and the wear rate. Specifically: A first aspect of the present invention provides a friction-reducing and wear-resistant sealing coating for ceramic-based composite materials, the friction-reducing and wear-resistant sealing coating comprising a transition layer adhered to a ceramic substrate layer and a 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer.
[0020] The ceramic substrate layer is preferably a C / SiC composite material layer; the transition layer is preferably a pure Si transition layer. Taking into account the matching degree between the thermal expansion coefficients of the substrate and the coating material, the present invention uses Si as a bonding transition layer to alleviate thermal mismatch, increase the bonding force between the coating and the substrate, and extend the service life of the coating. Finally, a gradient abradable sealing coating with a pure Si transition layer and a self-lubricating composite coating as the surface coating is formed.
[0021] Furthermore, the 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer is composed of the following raw material components in percentage by weight: 7wt% Y2O3-stabilized ZrO2 40%-45%, CaF2 35%-40%, Mo 6%-12%, and Ag 8%-14%.
[0022] Among them: the mass percentage of 7wt% Y2O3 stabilized ZrO2 can be, for example, 40%, 41%, 42%, 43%, 44%, 45%, etc.; the mass percentage of CaF2 can be, for example, 35%, 36%, 37%, 38%, 39%, 40%, etc.; the mass percentage of Mo can be, for example, 6%, 7%, 8%, 9%, 10%, 11%, 12%, etc.; the mass percentage of Ag can be, for example, 8%, 9%, 10%, 11%, 12%, 13%, 14%, etc.
[0023] The composition design concept of the self-lubricating layer of the present invention is derived from the synergistic lubrication effect between various lubricating phases. YSZ, as the matrix phase of the coating, is widely used in extreme environments due to its excellent high-temperature performance. Soft metal Ag has excellent lubrication performance at medium and low temperatures and has high thermal conductivity. It can also effectively protect the friction layer at high temperatures by reducing local heat. CaF2 has excellent lubrication performance at 800°C, but may volatilize during the preparation process due to its low melting point. After adding metal Mo, a chemical reaction will occur under the action of heat and force. The product CaMoO4 forms a friction layer with other lubricating substances, stably exists on the coating surface, and has obvious lubrication effect.
[0024] A second aspect of the present invention provides a method for preparing a friction-reducing and wear-resistant sealing coating for a ceramic-based composite material, comprising the following steps: Step 1: Select 7wt% Y2O3 stabilized ZrO2, CaF2, Mo and Ag powders as raw materials, and ball mill and mix them according to the raw material mass ratio of 7wt% Y2O3 stabilized ZrO2 40%-45%, CaF2 35%-40%, Mo 6%-12% and Ag 8%-14% respectively; The powder particle size of the raw materials is 40-150 μm, the ball milling parameters are rotation speed 150-200 Hz, ball milling time 0.5-1 h, and ball-to-material ratio 5:1.
[0025] Step 2: Drying the powder obtained in step 1 and the pure Si powder to pretreat the surface of the C / SiC composite material; The pretreatment process of the surface of the C / SiC composite material includes: grinding the surface of the C / SiC matrix with a 60-mesh diamond grinding disc, chamfering the edge, and finally ultrasonic cleaning and drying.
[0026] Step 3: Use pure Si powder to prepare a pure Si transition layer on the surface of the C / SiC composite material matrix, and use the mixed powder obtained in step 1 to prepare a 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer on the surface of the pure Si transition layer.
[0027] Preferably, the pure Si transition layer and the 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer are both prepared by supersonic plasma spraying.
[0028] The spraying parameters used for the pure Si transition layer are: spraying power 30-35Kw, powder feeding rate 1r / min, spraying distance 10cm, protective gas is argon, flow rate is 6L / min, and pressure is 1.05MPa; the spraying power used for the above-mentioned pure Si transition layer can be, for example, 30Kw, 31Kw, 32Kw, 33Kw, 34Kw, 35Kw, etc.
[0029] The spraying parameters used for the 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer are: 40-45Kw, 2r / min, spraying distance 10cm, protective gas is argon, flow rate is 6L / min, pressure is 1.05MPa, and the spraying power used for the above-mentioned self-lubricating layer can be, for example, 40Kw, 41Kw, 42Kw, 43Kw, 44Kw, 45Kw, etc.
[0030] The thickness of the pure Si transition layer finally prepared is 180-200μm, for example, it can be 180μm, 185μm, 190μm, 195μm, 200μm, etc.; the thickness of the self-lubricating layer is 400-500μm, for example, it can be 400μm, 420μm, 440μm, 460μm, 480μm, 500μm, etc.
[0031] After the above-mentioned friction-reducing and wear-resistant sealing coating is prepared, it is necessary to conduct high-temperature friction and wear performance testing: after the obtained coating is polished, it is tested on a friction machine to obtain the friction coefficient curve, and the coating wear volume is measured using a Bruker 3D profilometer to calculate the wear rate.
[0032] The equipment used for friction and wear performance testing is Rtec MFT-5000-H high temperature friction tester, and the sliding mode is reciprocating. Test parameters: grinding pair Al2O3, time about 15min, frequency 8-10Hz, stroke 4-5mm, temperature 390-410℃, 790℃-810℃.
[0033] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments: Example 1
[0034] A method for preparing a friction-reducing and wear-resistant sealing coating for a ceramic-based composite material comprises the following steps: S1. Using C / SiC composite material as the matrix, the C / SiC composite material cut to a size of 25mm×15mm×4mm was polished with a 60-mesh diamond grinding disc. After obtaining a certain roughness, the edge was chamfered to prevent the coating on the edge of the matrix from falling off due to excessive stress. The pretreated matrix material was ultrasonically cleaned and then placed in a vacuum drying oven at 100°C for 12 hours to make the surface clean and dry, and used as the matrix material; S2. Select 7YSZ, CaF2, Mo, Si and Ag powders as raw materials, and the powder particle sizes are D=100μm, D=75μm, D=75μm, D=75μm, and D=48μm respectively. Weigh each raw material according to the mass ratio of 7YSZ:CaF2:Mo:Ag=40%:40%:8%:12%. The process is carried out in a glove box, and then put the mixed powder and zirconia balls with a diameter of 4mm into a ball mill according to a ball-to-material ratio of 5:1. Set the ball milling parameters: speed 180Hz, forward rotation for 10 minutes, reverse rotation for 10 minutes, pause for 2 minutes in the middle, a total of 1h. After uniform mixing, use a sieve to separate the balls and powder, place the sieved powder in a vacuum drying oven, and keep it at 80℃ for 6h with the powder Si required for the bonding layer. Finally, put the dried powder into a vacuum bag and seal it for storage.
[0035] S3. Put pure Si powder and evenly mixed powder into the powder feeder of supersonic plasma spraying HEPJ-II equipment, and set the powder feeding rate to 1r / min and 2r / min respectively. Place the substrates in the fixture on the operating table in turn, and prepare the bonding layer Si first. Set the spraying parameters as follows: laser power 35W, spraying distance 10cm, spray gun moving rate 1800cm / min, superposition cycle 15 times, protective atmosphere is argon, powder feeding gas flow rate is set to 6L / min, and pressure is 1.05MPa. After the bonding layer is prepared and cooled, clean the surface and prepare the ceramic-based composite coating on the surface. Set the spraying parameters as follows: laser power 42W, spraying distance 10cm, spray gun moving rate 1800cm / min, superposition cycle 45 times, protective atmosphere is argon, powder feeding gas flow rate is set to 6L / min, and pressure is 1.05MPa. After the sample is cooled, a YSZ ceramic-based abradable sealing coating sample is obtained.
[0036] S4. High temperature friction and wear test: A high temperature friction and wear tester (Rtec MFT-5000-H) was used to perform the friction and wear test. The sample was clamped and fixed with a fixture. The Al2O3 ball (Ø=9.525) was used for the grinding pair. The test temperature was 400℃, the load was 5N, the frequency was 10Hz, and the displacement amplitude was 5mm. After 15 minutes, the friction and wear test was completed. The wear volume of the sample was tested using a three-dimensional optical profiler from Bruker and the wear rate was calculated. Example 2
[0037] A method for preparing a friction-reducing and wear-resistant sealing coating for a ceramic-based composite material comprises the following steps: S1. Using C / SiC composite material as the matrix, the C / SiC composite material cut to a size of 25mm×15mm×4mm was polished with a 60-mesh diamond grinding disc. After obtaining a certain roughness, the edge was chamfered to prevent the coating on the edge of the matrix from falling off due to excessive stress. The pretreated matrix material was ultrasonically cleaned and then placed in a vacuum drying oven at 100°C for 12 hours to make the surface clean and dry, and used as the matrix material; S2. 7YSZ, CaF2, Mo, Si and Ag powders were selected as raw materials, and the powder particle sizes were D=100μm, D=75μm, D=75μm, D=75μm, and D=48μm, respectively. The raw materials were weighed in a glove box according to the mass ratio of 7YSZ:CaF2:Mo:Ag=40%:40%:11%:9%, and then the mixed powder and zirconia balls with a diameter of 4mm were placed in a ball mill according to a ball-to-material ratio of 5:1. The ball milling parameters were set as follows: speed 180Hz, forward rotation for 10 minutes, reverse rotation for 10 minutes, pause for 2 minutes in the middle, and a total of 1h. After uniform mixing, the balls and powder were separated with a sieve, and the sieved powder was placed in a vacuum drying oven, and kept at 80℃ for 6h with the powder Si required for the bonding layer. Finally, the dried powder was placed in a vacuum bag and sealed for storage.
[0038] S3. Put pure Si powder and evenly mixed powder into the powder feeder of supersonic plasma spraying HEPJ-II equipment, and set the powder feeding rate to 1r / min and 2r / min respectively. Place the substrates in the fixture on the operating table in turn, and prepare the bonding layer Si first. Set the spraying parameters as follows: laser power 35W, spraying distance 10cm, spray gun moving rate 1800cm / min, superposition cycle 15 times, protective atmosphere is argon, powder feeding gas flow rate is set to 6L / min, and pressure is 1.05MPa. After the bonding layer is prepared and cooled, clean the surface and prepare the ceramic-based composite coating on the surface. Set the spraying parameters as follows: laser power 45W, spraying distance 10cm, spray gun moving rate 1800cm / min, superposition cycle 45 times, protective atmosphere is argon, powder feeding gas flow rate is set to 6L / min, and pressure is 1.05MPa. After the sample is cooled, a YSZ ceramic-based abradable sealing coating sample is obtained.
[0039] S4. High temperature friction and wear test: A high temperature friction and wear tester (Rtec MFT-5000-H) was used to perform the friction and wear test. The sample was clamped and fixed with a fixture. The Al2O3 ball (Ø=9.525) was used for the grinding pair. The test temperature was 800℃, the load was 5N, the frequency was 10Hz, and the displacement amplitude was 5mm. After 15 minutes, the friction and wear test was completed. The wear volume of the sample was tested using a three-dimensional optical profiler from Bruker and the wear rate was calculated.
[0040] Figure 1 The cross-sectional morphology of the gradient YSZ ceramic-based abradable sealing coating prepared by supersonic plasma spraying in Example 1 in the backscattering mode. It can be observed that the thickness of the transition layer of the gradient composite coating is about 180μm, and the self-lubricating layer is about 485μm. The coating presents a typical layered structure after spraying, and different phases present different contrasts. There are no obvious defects such as cracks and holes, the organization is relatively dense, and the surface ceramic-based composite coating and the Si bonding layer, and the Si bonding layer and the C / SiC composite material matrix are tightly bonded.
[0041] Figure 2 The curve of the friction coefficient of the YSZ ceramic-based abradable sealing coating in Example 1 under 400°C environment changes with time. Figure 2 It can be seen from the friction coefficient curve that the friction coefficient of the ceramic-based abradable sealing coating is only about 0.35 at 400°C. This is mainly because soft metal Ag is added to the coating. The sliding deformation of pure metal Ag is easy at high temperature, thus significantly reducing friction damage.
[0042] Figure 3 The wear rate of the wear spot of the YSZ ceramic-based abradable sealing coating in Example 1 was measured and calculated by a three-dimensional profilometer after the friction and wear test at 400°C. The average wear rate of the YSZ ceramic-based abradable sealing coating at 400°C is 1.03×10 -7 mm 3 / (N·m), which means that when the coating contacts the grinding pair, it can not only reduce wear but also has excellent wear resistance.
[0043] Figure 4 The cross-sectional morphology of the gradient YSZ ceramic-based abradable sealing coating prepared by supersonic plasma spraying in the backscattering mode in Example 2. It can be observed that the thickness of the YSZ layer and the thickness of the Si bonding layer are not much different from those in Example 1, and the coating also presents a typical layered structure after spraying, with good bonding between layers and between phases, and no macroscopic defects, which shows that the process of preparing the coating by supersonic plasma spraying is relatively stable and the prepared coating has a high quality.
[0044] Figure 5 The curve of the friction coefficient of the YSZ ceramic-based abradable sealing coating in Example 2 under 800°C environment changes with time. Figure 5It can be seen from the friction coefficient curve that the friction coefficient of the ceramic-based abradable sealing coating is only about 0.29 at 800°C. This shows that the ceramic-based abradable sealing coating prepared by this method has a low friction coefficient under different high-temperature environments and can achieve excellent wear reduction effects. This is directly related to the composition design of the coating. The matrix phase YSZ in the coating has excellent high-temperature stability and a certain load-bearing capacity, and at high temperatures, the self-lubricating phase CaMoO4 is generated in situ. These calcium salts are gradually compacted and filled into the wear surface during the reciprocating sliding process with fluorides, Ag, etc., forming a strong, continuous, and smooth protective film, which hinders the continuous damage of the coating to the grinding pair and effectively reduces the friction damage of the coating at 800°C. It is precisely because of the good synergistic lubrication between different lubricating phases in the coating that the coating achieves excellent wear reduction and wear resistance effects at different test temperatures.
[0045] Figure 6 The wear rate of the wear spot of the YSZ ceramic-based abradable sealing coating in Example 2 was measured and calculated by a three-dimensional profilometer after the friction and wear test at 800°C. The average wear rate of the YSZ ceramic-based abradable sealing coating at 800°C is 1.03×10 -7 mm 3 / (N·m), which means that when the coating contacts the grinding pair, the friction layer formed on the surface effectively protects the coating and reduces friction and wear. This ensures that when the coating is applied to the outer ring of the turbine, it can not only effectively reduce wear and protect the blades, but also maintain a long life and will not fail due to falling off or peeling.
[0046] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0047] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A friction-reducing and wear-resistant sealing coating for ceramic-based composite materials, characterized in that: The friction-reducing and wear-resistant sealing coating consists of a transition layer adhered to a ceramic substrate layer and a 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer.
2. The friction-reducing and wear-resistant sealing coating for ceramic-based composite materials according to claim 1, characterized in that: The ceramic matrix layer is a C / SiC composite material layer; and / or the transition layer is a pure Si transition layer.
3. The friction-reducing and wear-resistant sealing coating for ceramic-based composite materials according to claim 1, characterized in that: The 7wt% Y2O3 stabilized ZrO2-based self-lubricating layer is composed of the following raw material components in percentage by weight: 7wt% Y2O3 stabilized ZrO2 40%-45%, CaF2 35%-40%, Mo 6%-12%, and Ag 8%-14%.
4. A method for preparing a friction-reducing and wear-resistant sealing coating for a ceramic-based composite material, characterized in that: The steps include: Step 1: Select 7wt% Y2O3 stabilized ZrO2, CaF2, Mo and Ag powders as raw materials, and ball mill and mix them according to the raw material mass ratio of 7wt% Y2O3 stabilized ZrO2 40%-45%, CaF2 35%-40%, Mo 6%-12% and Ag 8%-14% respectively; Step 2: Drying the powder obtained in step 1 and the pure Si powder to pretreat the surface of the C / SiC composite material; Step 3: Use pure Si powder to prepare a pure Si transition layer on the surface of the C / SiC composite material matrix, and use the mixed powder obtained in step 1 to prepare a 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer on the surface of the pure Si transition layer.
5. The method for preparing the friction-reducing and wear-resistant sealing coating for ceramic-based composite materials according to claim 4, characterized in that: In step 1, the powder particle size of the raw materials is 40-150 μm, the ball milling parameters are a rotation speed of 150-200 Hz, a ball milling time of 0.5-1 h, and a ball-to-material ratio of 5:
1.
6. The method for preparing the friction-reducing and wear-resistant sealing coating for ceramic-based composite materials according to claim 4, characterized in that: The pretreatment process of the surface of the C / SiC composite material in step 2 includes: The surface of the C / SiC substrate was polished with a diamond grinding disc, and the edges were chamfered, and finally ultrasonically cleaned and dried.
7. The method for preparing the friction-reducing and wear-resistant sealing coating for ceramic-based composite materials according to claim 4, characterized in that: In step 3, the pure Si transition layer and the 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer are both prepared by supersonic plasma spraying.
8. The method for preparing the friction-reducing and wear-resistant sealing coating for ceramic-based composite materials according to claim 7, characterized in that: The spraying parameters used for the pure Si transition layer are: spraying power 30-35Kw, powder feeding rate 1r / min, spraying distance 10cm, protective gas is argon, flow rate is 6L / min, and pressure is 1.05MPa.
9. The method for preparing the friction-reducing and wear-resistant sealing coating for ceramic-based composite materials according to claim 7, characterized in that: The spraying parameters used for the 7wt% Y2O3-stabilized ZrO2-based self-lubricating layer are: spraying power 40-45Kw, powder feeding rate 2r / min, spraying distance 10cm, protective gas is argon, flow rate is 6L / min, and pressure is 1.05MPa.
10. The method for preparing the friction-reducing and wear-resistant sealing coating for ceramic-based composite materials according to claim 4, characterized in that: The thickness of the pure Si transition layer prepared in step 3 is 180-200 μm, and the thickness of the self-lubricating layer is 400-500 μm.
Citation Information
Patent Citations
Automatic preparation method of long-service-life cylinder-like crystal structural thermal barrier coating on surface of guide blade of hot end part of fuel machine
CN104233178A
Ceramic-based composite turbine outer ring high-temperature sealing coating and preparation process thereof
CN109371353A
Self-healing high-density environmental barrier coating as well as preparation method and application thereof
CN114276169A
Ceramic-based sealing coating for surface of silicon carbide fiber reinforced silicon carbide composite material as well as preparation method and application of ceramic-based sealing coating
CN115340410A
Abradable seal coating with low friction coefficient and high volume wear rate and preparation method thereof
CN116535243A
